Galaxy pairs in the Sloan Digital Sky Survey – XV. Properties of ionized outflows. Issue 4 (2nd June 2022) - Matzko, William; Satyapal, Shobita; Ellison, Sara L; Sexton, Remington O; Secrest, Nathan J; Canalizo, Gabriela; Blecha, Laura; Patton, David R; Scudder, Jillian M
ABSTRACT: Powerful outflows are thought to play a critical role in galaxy evolution and black hole growth. We present the first large-scale systematic study of ionized outflows in paired galaxies and post-mergers compared to a robust control sample of isolated galaxies. We isolate the impact of the merger environment to determine if outflow properties depend on merger stage. Our sample contains ∼4000 paired galaxies and ∼250 post-mergers in the local universe (0.02 ≤ z ≤ 0.2) from the Sloan Digital Sky Survey Data Release 7 ( SDSS DR 7) matched in stellar mass, redshift, local density of galaxies, and [O iii ] λ5007 luminosity to a control sample of isolated galaxies. By fitting the [O iii ] λ5007 line, we find ionized outflows in ∼15 per cent of our entire sample. Outflows are much rarer in star-forming galaxies compared to active galactic nuclei (AGNs), and outflow incidence and velocity increase with [O iii ] λ5007 luminosity. Outflow incidence is significantly elevated in the optical + mid-infrared selected AGN compared to purely optical AGN; over 60 per cent show outflows at the highest luminosities ($L_{[OIII]~λ 5007}\, \gtrsim$ 10 42 erg s −1 ), suggesting mid-infrared AGN selection favours galaxies with powerful outflows, at least for higher [O iii ] λ5007 luminosities. However, we find no statistically significant difference in outflow incidence, velocity, and luminosity in mergers compared to isolated galaxies, and there is no dependence on merger stage. Therefore, while interactions are predicted to drive gas inflows and subsequently trigger nuclear star formation and accretion activity, when the power source of the outflow is controlled for, the merging environment has no further impact on the large-scale ionized outflows as traced by [O iii ] λ5007.